Transformational Leadership, Work Motivation, and School Climate as Predictors of Teacher Performance: A Quantitative Study in Public Primary Schools of Tempel Subdistrict, Sleman Regency, Indonesia - Kurniasari, Evi; Yuliana, Lia; Ikhwan, Muh. Saidil (Journal of Innovation and Research in Primary Education, 2025)
This study investigates the influence of principal leadership, work motivation, and school climate on the performance of teachers in public elementary schools across Tempel Subdistrict, Sleman Regency, Special Region of Yogyakarta, Indonesia. Adopting a quantitative research approach with an explanatory design, the study involved 118 teachers selected through simple random sampling from a population of 168. Data were collected via structured questionnaires that had undergone validity and reliability testing, and analyzed using descriptive statistics and multiple linear regression, supported by classical assumption tests (normality, linearity, multicollinearity, and heteroscedasticity). The results reveal that (1) principal leadership and work motivation significantly influence teacher performance (F = 50.166, p < 0.05), (2) principal leadership and school climate also significantly affect teacher performance (F = 32.857, p < 0.05), (3) work motivation and school climate together contribute significantly to teacher performance (F = 49.393, p < 0.05), and (4) all three variables  such as principal leadership, work motivation, and school climate – simultaneously have a significant effect on teacher performance (F = 35.413, p < 0.05). These findings underscore the importance of a holistic leadership strategy that fosters intrinsic motivation and cultivates a supportive school climate to enhance teacher productivity. This study provides empirical insights that can inform school leaders and education policymakers in developing sustainable, evidence-based strategies to improve instructional quality in Indonesian primary schools, particularly in rural and suburban educational contexts. However, it is important to note the study's limitations, including its focus on a single district, which may limit generalizability, and the reliance on self-reported data, which may introduce bias. Practical indicators such as teacher training, school leadership programs, and climate enhancement interventions could be explored in future research.